Effect of Synovex-H and Ralgro implants on weight gain of heifers grazing wheat pasture - Laudert, S.; Nelson, R. (Kansas State University. Agricultural Experiment Station, 2011)
Heifer calves grazing winter wheat pasture and implanted with Synovex-H or Ralgro gained 18 and 14% faster (P<.01) respectively, than heifers not implanted. Weight gains were similar for both implants.
Keywords: Beef; Synovex-H; Ralgro; Implants; Gain; Wheat pasture